Dwarf oil palm for future generation - Murugesan, P; Kumar, K Sunil (Indian Horticulture, 2019)
There are five genetic stocks (three from Elaies oleifera and two from Elaeis guineensis) with compact characteristics with moderate yield potential have been developed in India. Currently interspecific hybrids and progenies developed from the identified genetic stocks are being evaluated in the field trial to develop compact varieties.